1982
DOI: 10.3402/tellusa.v34i4.10823
|View full text |Cite
|
Sign up to set email alerts
|

Stratospheric HTO and <sup>95</sup>Zr residence times

Abstract: The depletion of the stratospheric burdens of particulate "'Zr for times up to around 1 year, and gaseous HTO for times up to 3 years, attributed to the November 17, 1976 Chinese high-yield test indicates that both have about the same residence half-time (10 months). The indications are that gravitational settling of particles in the lower stratosphere can be considered to be negligible in studying transport processes. The rate of depletion of the stratospheric burden of HTO from the high-yield Chinese test of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Finally, there was a larger test on 27.6.1973, which could have influenced the balloon data. It released 19 MCi HTO, 95% of which remained below 20 km altitude [ Mason et al , 1982]. Much of that HTO had been removed before the date of the first balloon flight on 14.6.1975, such that the impact of that test explosion on these data should have been a factor of 10 lower than that of the explosion on 17.11.1976 on those obtained from the flight on 14.8.1977, i.e., it should be negligible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, there was a larger test on 27.6.1973, which could have influenced the balloon data. It released 19 MCi HTO, 95% of which remained below 20 km altitude [ Mason et al , 1982]. Much of that HTO had been removed before the date of the first balloon flight on 14.6.1975, such that the impact of that test explosion on these data should have been a factor of 10 lower than that of the explosion on 17.11.1976 on those obtained from the flight on 14.8.1977, i.e., it should be negligible.…”
Section: Discussionmentioning
confidence: 99%
“…The reason probably is that the initial radioactive cloud of these explosions remained below 20 km altitude and further, that the lower stratosphere at mid latitudes is rapidly flushed by exchange with the troposphere. For example, Mason et al [1982] found that the HTO injected by the test explosion in 1976 was removed from the lower stratosphere with an e‐fold time of 1.2 years. As a consequence, only a small fraction of the so‐injected HTO penetrated to higher altitudes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that a major removal process is by transport to polar latitudes and deposition via subsidence onto the polar ice caps [Hammer et al, 1980]. Mason et al [1982] suggest stratospheric residence times of 13.7 and 14.6 months for 95Zr and tritiated water (HTO), respectively, from Chinese nuclear weapons tests. The amount of material and its relative distribution among ash, sulfate, and sulfurous precurser gases will also affect the removal rate to the extent that there are corresponding variations in aerosol size distributions.…”
Section: Stratospheric Sulfate Aerosol Removal Ratementioning
confidence: 99%
“…Another condition may be in the presence of large amount of airborne particles in the lower stratosphere and AME layer which is injected by recent volcanic activities. In this connection, Mroz et al (1983) Mason (1985) suggests that a more likely reason for the faster removal of HTO is alternation of the stratosphere-troposphere exchange rate by the radiative effect of the sulfate aerosol injected into the stratosphere by large-scale volcanic eruptions. The heating of the atmosphere in the 30mb region as a result of the additional volcanic aerosol after the E1 Chichon eruption has been reported by Quiroz (1983) and at 30 and 50mb by Labitzke et al (1983).…”
Section: Comparison Between the Calculated Andmentioning
confidence: 99%
“…Mason (1985) has observed that the depletion of the HTO burden in the stratosphere in 1982 showed an anomalous rate in comparison with other years which has the apparent characteristic time of 7.8 months, roughly half of the normal residence time. The transport process involving such a short residence time cannot be explained by a simple scavenging model with the apparent residence time of about one year.…”
Section: Introductionmentioning
confidence: 99%